Oxidative stress: An essential factor in the process of arteriovenous fistula failure - Hu, Ke; Guo, Yi; Li, Yuxuan; Lu, Chanjun; Cai, Chuanqi; Zhou, Shunchang; Ke, Zunxiang; Li, Yiqing; Wang, Weici (Frontiers in Cardiovascular Medicine, 2022)
For more than half a century, arteriovenous fistula (AVFs) has been recognized as a lifeline for patients requiring hemodialysis (HD). With its higher long-term patency rate and lower probability of complications, AVF is strongly recommended by guidelines in different areas as the first choice for vascular access for HD patients, and its proportion of application is gradually increasing. Despite technological improvements and advances in the standards of postoperative care, many deficiencies are still encountered in the use of AVF related to its high incidence of failure due to unsuccessful maturation to adequately support HD and the development of neointimal hyperplasia (NIH), which narrows the AVF lumen. AVF failure is linked to the activation and migration of vascular cells and the remodeling of the extracellular matrix, where complex interactions between cytokines, adhesion molecules, and inflammatory mediators lead to poor adaptive remodeling. Oxidative stress also plays a vital role in AVF failure, and a growing amount of data suggest a link between AVF failure and oxidative stress. In this review, we summarize the present understanding of the pathophysiology of AVF failure. Furthermore, we focus on the relation between oxidative stress and AVF dysfunction. Finally, we discuss potential therapies for addressing AVF failure based on targeting oxidative stress.